Evaluation of antibacterial, antioxidant and toxicological activities of crude extracts of Calotropis gigantean, Mimosa pudica, Achyranthes aspera and Hibiscus rosa-siensis variety: Kalyani from Faridpur, Bangladesh - Nushrat, Nayeema (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2011